Military Leadership : In Pursuit of Excellence - Edited By Rosenbach, William E. and Taylor, Robert L. and Foreword by Gregory S. Newbold (Lahore Service Book Club, 2005)
An anthology of classic and contemporary articles, as well as original essays, on leaders, followers, and the personal and organizational values that promote effective military leadership.
Keywords: Leadership -- Command of troops